Issues and Challenges of Intelligent Systems and Computational Intelligence - Kóczy, László T.; Kóczy, László T.; Pozna, Claudiu R.; Pozna, Claudiu R.; Kacprzyk, Janusz.; Kacprzyk, Janusz. (Studies in Computational Intelligence,, 2014)
This carefully edited book contains contributions of prominent and active researchers and scholars in the broadly perceived area of intelligent systems. The book is unique both with respect to the width of coverage of tools and techniques, and to the variety of problems that could be solved by the tools and techniques presented. The editors have been able to gather a very good collection of relevant and original papers by prominent representatives of many areas, relevant both to the theory and practice of intelligent systems, artificial intelligence, computational intelligence, soft computing, and the like. The contributions have been divided into 7 parts presenting first more fundamental and theoretical contributions, and then applications in relevant areas.        .